Effects of environmental conditions on the axial tension–compression fatigue behavior of carbon/epoxy plain-weave laminates containing flaws. (November 2020) - Deluy, Marc-Claudel; Khay, Mohamed; Ngo, Anh Dung; Dubé, Martine; Ganesan, Rajamohan
The objective of this work is to investigate the effects of environmental conditions on the axial fatigue behavior of a carbon/epoxy plain-weave laminate with an embedded flaw subjected to a partially reversed cyclic load (stress ratio R  = −0.1) in tension–compression. This specific material is more commonly used in aerospace engineering for the manufacturing of aircraft structural parts, which are directly exposed to various environmental conditions during service. Specific environmental and loading conditions that are appropriate to simulate real-life conditions are considered to observe and collect information about the material's behavior. For the investigation, dry and wet coupons were submitted to room temperature, 82 and 121 ℃ under loading frequencies of 7 and 15 Hz. A maximum allowable strain increase criterion is used to monitor the flaw growth threshold or delamination onset, during fatigue testing. The ultrasonic imaging (C-scan) technique is used to verify and confirm the delamination onset. Results show that the delamination onset strain increase criterion, along with fatigue life, generally decreased as the operating temperature and humidity were increased and that frequency had little effect on the delamination onset fatigue life. The S – N curves obtained from the tension–compression fatigue data were then compared to those of a previous work carried out in tension–tension fatigue loading. Results show a clear degradation in the delamination onset fatigue life of the coupons tested under tension–tension cyclic loading when the minimum tensile component of the cyclic load was replaced with a compressive load of the same magnitude.